Comparative Sensitivity of Tissue Cultures to Rubella Virus: Use of Guinea Pig Cells for Virus Titration - Horta-Barbosa, L. (1969)
A series of 19 different primary and serial tissue cultures were investigated for their sensitivity to virulent or attenuated rubella virus (RV). Primary guinea pig tissues, a serial passage of baby hamster kidney, and primary human amnion were comparable to African green monkey kidney tissue cultures in their sensitivity. In general, primary human tissues were relatively insusceptible to the Gilchrist strain of RV. RV interfered with the growth of vesicular stomatitis virus. Based on this finding, it was possible to develop an assay method in guinea pig tissue cultures by using VSV as the challenge virus. This system appeared to be comparable in sensitivity to the use of primary monkey kidney tissue cultures for the detection of small amounts of RV and offers the advantages of economy, rapidity, and safety.